The wounds of nations : Horror cinema, historical trauma and national identity. - Blake, Linnie (Manchester University Press, 2008)
The wounds of nations explores the ways in which horror films allows international audiences to deal with the horrors of recent history? from genocide to terrorist outrage, nuclear war to radical political change. Far from being mere escapism or titillation, it shows how horror (whether it be from 1970s America, 1980s Germany, post-Thatcherite Britain or post-9/11 America) is in fact a highly political and potentially therapeutic film genre that enables us to explore, and potentially recover from, the terrors of life in the real world. Exploring a wide range of stylistically distinctive and ge.